Towards the bioproduction of methacrylic acid: a case study on the use of decarboxylases - Rossoni, Luca (2016)
In this study, the biocatalytic production of methacrylic acid (MAA), a commodity chemical with a large global market, was investigated. The target was to develop MAA formation via enzymatic decarboxylation of itaconic, mesaconic, citraconic and citramalic acid. Several candidate enzymes were tested, but none catalysed the target reactions. Therefore, a novel high throughput screening method for decarboxylases was developed to enable protein engineering. The screening assay detected gaseous CO2 with a pH-dependent colorimetric reaction, in a 96-well format. Focused mutagenesis was then performed on the mevalonate diphosphate decarboxylases (MVD) from Saccharomyces cerevisiae and from Picrophilus torridus. However, MAA formation was not observed, even after screening over 3800 variants. Further investigation was then performed on some of the candidates to understand why MAA was not formed and to develop alternative strategies for enzyme selection. P. torridus MVD was discovered to belong to a new class of enzymes, mevalonate-3-kinase, and to be part of a novel archaeal mevalonate pathway. The enzyme also catalysed the formation of isobutene from 3-hydroxyisovalerate with unprecedented production rates. S. cerevisiae and Aspergillus niger phenylacrylic acid decarboxylases, previously believed to be cofactor-free enzymes, were proposed to require divalent metals and a novel organic cofactor. The enzymatic mechanism of Pseudomonas fluorescens α-amino-β-carboxymuconate-ε-semialdehyde (ACMS) decarboxylase was investigated. Through inhibition studies, it was demonstrated that the aldehyde and amino moieties of ACMS could be directly involved in catalysis, in contrast to the previously reported mechanism. This information partially explains why some of these candidates could not catalyse the target reaction, and provides insights into their potential future use for the bioproduction of MAA. Although this route does not seem feasible at present, this study gives foundation and guidance for future investigations.